WALTER SCOTT: PIONEERING THE HISTORICAL NOVEL GENRE IN ENGLISH LITERATURE - UMIRZOQOVA SHAXRIZODA MIRXALIL QIZI; KHAMITOV ELDORBEK ERKIN O'GLI (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract:Walter Scott stands as a seminal figure in English literature, particularly renowned for his groundbreaking contributions to the historical novel genre. This article explores Scott's influential role as a founder figure in shaping and popularizing historical fiction, examining his innovative narrative techniques, thematic exploration, and enduring literary legacy.